Walking the Talk, from Online to Offline? Analyzing Predictors of Political Engagements in the Case of Cebu City, Philippines - Noe John Joseph Endencio Sacramento (Universitas Muhammadiyah Ponorogo, 2021)
The political engagement of individuals has complexly evolved in a borderless world brought by various developments in technology. This study revisits how various predictors, including personality traits such as extraversion and openness to experience, political efficacy, and online (FB) engagement, influence offline political engagements. Using quantitative techniques, the data gathered from a survey with 120 respondents in Cebu City, Philippines, was analyzed using the R software to generate descriptive statistics, correlation, simple linear regression, and multiple regression. A salient finding shows that the respondents’ level of extraversion, openness to experience, and political efficacy is high, while the level of political engagement is low online and offline. While online (FB) political engagement alone highly predicts offline political engagement behavior, all other independent variables (extraversion, openness to experience, and political efficacy) modeled as one attributes a very low effect towards offline political engagement. The model that includes all predictors have produced significant result that strongly supports this study’s central claim. Further, the study discussed the non-engagement of Cebuanos and commenced with suggestions on how Facebook (FB) can further influence an individual’s political engagements as a social media platform. While the publics’ engagements on political issues are vital to democratic societies, the study stressed social media's crucial influence on safeguarding democracies, human rights, and social justice.